The Routledge Handbook of Global Islam and Consumer Culture - Krawietz, Birgit; Gauthier, François (Routledge Handbooks in Religion, 2024)
The Routledge Handbook of Global Islam and Consumer Culture is an outstanding inter- and transdisciplinary reference source to key topics, problems, and debates in this challenging research field. The study of Islam is enriched by investigating religion and, notably, Islamic normativity (fiqh) as a resource for product design, attitudes toward commodification, and appropriated patterns of behavior. Comprising 35 chapters (including an extended Introduction) by a team of international contributors from chairholders to advanced graduate students, the handbook is divided into seven parts: Guiding Frameworks of Understanding Historical Probes Urbanism and Consumption Body Manipulation, Vestiary Regimes, and Gender Mediated Religion and Culture Consumer Culture, Lifestyle, and Senses of the Self through Consumption Markets These sections examine vibrant debates around consumption, frugality, Islamic jurisprudence and fatwas in the world economy, capitalism, neoliberalism, trade relations, halalization, (labor) tourism and travel infrastructure, body modification, fashion, self-fashioning, lifestylization, Islamic kitsch, urban regeneration, heritage, Islamic finance, the internet, and Quran recitation versus music. Contributions present selected case studies from countries across the world, including China, Indonesia, Malaysia, Morocco, Nigeria, Qatar, Pakistan, and Turkey. The handbook is essential reading for students and researchers in Islamic studies, Near and Middle Eastern studies, religious studies, and cultural studies. The handbook will also be very useful for those in related fields, such as politics, area studies, sociology, anthropology, and history.